ANALISIS LQ (LOCATION QUOTIENT ) KOMODITI TANAMAN JAGUNG DI KECAMATAN TANJUNG LAGO KABUPATEN BANYUASIN - Henny Malini; Marwan Sufri; Selly Oktarina (Agribusiness Study Program Universitas Sriwijaya in Collaboration with Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2018)
Superior commodities (bases) need to be developed optimally because they have comparative advantages that can improve the economy and income of economic actors. Comparative advantage possessed by a commodity can encourage the creation of competitive advantage (competitive advantage) to similar commodities in a region. These advantages provide benefits to commodities in winning the market competition (Tarigan, 2009). The purpose of this research is to determine whether corn is the economic base of Tanjung Lago Sub-district of Banyuasin Regency. Regarding whether corn commodities include base or non economic base, the analytical tool used is location quotient analysis method (LQ). Development of corn crops is the second economic activity activity after rice plant in Tanjung Lago Sub-district of Banyuasin with Location Quotient value of 1 (LQ> 1) means the development of corn crop commodity is one of determinant factor in overall economic development in Tanjung Lago Sub-district of Banyuasin Regency . Corn production is able to meet the needs of its own region and other areas in South Sumatra.